Postoperative Care in Facial Implants - Floyd, Elizabeth Mia; Eppley, Barry; Perkins, Stephen W. (Facial Plastic Surgery, 2018)
Facial augmentation is a growing field, secondary to the appreciation of the changes seen in the facial skeleton with aging and the growing acceptance/popularity of facial fat grafting and facial fillers. In addition, it plays a significant role in patients with congenital facial deficiencies as well as those interested in facial feminization/masculinization surgery. Several facial implants are discussed in this article including classic facial implants such as malar, submalar, chin, and prejowl implants as well as newer facial implants such as mandible, temporal, forehead, and skull implants. Special care is given to the postoperative care of these implants. Custom-made implants with three-dimensional computed tomography reconstruction are also discussed
Keywords: facial implant; facial augmentation; cheek augmentation; midface augmentation; chin implant; prejowl implant; mandible implant; temporal implant